Heathlands, fire and grazing. A palaeoenvironmental view of Las Hurdes (Cáceres, Spain) history during the last 1200 years - Abel-Schaad, Daniel; López-Sáez, José A.; Pulido, Fernando (Forest Systems, 2014)
Aim of study. The diachronic study of vegetation change through palynological analysis of sedimentary deposits is an essential tool both to design sound strategies on landscape  management and to understand its anthropogenic dynamics.Area of study. La Meseguera mire (Ladrillar, Cáceres, Spain) is located in the Hurdes region in the western part of Iberian Central System and started to develop at the beginning of the Islamic period (ca. 770 cal AD), in an area widely dominated by heathland.  Material and methods. Pollen, non-pollen palynomorphs and charcoal accumulation rate (CHAR) combined with historical data are useful indicators to assess the increasing role of human influence on vegetation.Main results. The use of fire and livestock husbandry represents the main drivers of landscape change in the course of the history. The establishment of forest afforestation plans, from the middle of 20th century, changed substantially the regional features. The sporadic presence of beech pollen is detected until 16th century, which implies the most western location in the Iberian Central Mountain System.Research highlights. The integration of pollen analysis and historical data is an essential tool when studying the changes in Holocene vegetation. These changes have been mainly driven by anthropogenic disturbances, more specifically by fire and livestock husbandry.Key Words: Anthropogenic dynamics; Central Mountain System; microcharcoals; non-pollen palynomorphs.